IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Yulyani Yulyani; Tiara Kazumaretha; Yossa Arisanti; Yanti Fitria; Desyandri Desyandri (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The objectives in this study are 1) to find out the implementation of pedagogical competence of teachers in thematic learning in SD Negeri 06 Kampung Lapai, 2) to find out the obstacles or problems experienced by teachers in implementing the pedagogical competence of teachers in thematic learning at SD Negeri 06 Kampung Lapai, 3) to find solutions to overcome obstacles in implementing teacher pedagogical competence in thematic learning at SD Negeri 06 Kampung Lapai. The method in this research is descriptive method with a qualitative approach. Data collection techniques used are observation, interviews, and also documentation. The results of the study that can be concluded are the implementation of teacher pedagogical competencies in thematic learning at SD Negeri 06 Kampung Lapai is already good, although there are some obstacles in applying it such as different teacher education backgrounds, weak methods and the use of instructional media. The efforts to overcome the problems that occur are by conducting functional training and teacher competence in the beginning of the new school year, and motivating teachers so that teachers can improve the learning process process for the better.Keywords: Implementation, Pedagogical competence,thematic learning.